Modernisasi Pendidikan Islam Ala Soekarno - Siti Zubaedah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: For Soekarno, Islamic education, as education in general is an arena to sharpen the mind, sharpen the mind, and develop the intellect. Soekarno said that the essential motor of the rethinking of Islam is the return of respect for reason. In addition, islamic education witi be able to grow and move forward if there is a position of equatity between women and men, teachers who are quatified and actually able to become an educator (not just teachers) are constantly thinking about the progress of their students to be able to face her future, and the presence of education system that is mutuatism. Mutual interaction led to a creative, critical, promote dialogue, as well as distance learners from an authoritarian cutture. Keywords : Soekarno, Islamic education, modernization.